2010
DOI: 10.1039/c0cp00586j
|View full text |Cite
|
Sign up to set email alerts
|

One-pot electrodeposition, characterization and photoactivity of stoichiometric copper indium gallium diselenide (CIGS) thin films for solar cells

Abstract: Herein we report the one-pot electrodeposition of copper indium gallium diselenide, CuIn(1-x)Ga(x)Se(2) (CIGS), thin films as the p-type semiconductor in an ionic liquid medium consisting of choline chloride/urea eutectic mixture known as Reline. The thin films were characterized by scanning electron microscopy with energy dispersive X-ray analysis, transmission electron microscopy, X-ray photoelectron spectroscopy, Raman microspectroscopy, and UV-visible spectroscopy. Based on the results of the characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…Harati et al fabricated successfully stoichiometric CIGS thin film by the one-pot electrodeposition in Reline as electrolyte. 21 Malaquias et al used Reline to deposit In-Ga on Cu and Mo electrodes and finally obtained solar cell with a 7.9% efficiency. 15 Chen at al reported a 3.87% CZTS solar cell efficiency by co-electrodepositing Cu-Zn-Sn precursor thin films in Reline.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Harati et al fabricated successfully stoichiometric CIGS thin film by the one-pot electrodeposition in Reline as electrolyte. 21 Malaquias et al used Reline to deposit In-Ga on Cu and Mo electrodes and finally obtained solar cell with a 7.9% efficiency. 15 Chen at al reported a 3.87% CZTS solar cell efficiency by co-electrodepositing Cu-Zn-Sn precursor thin films in Reline.…”
mentioning
confidence: 99%
“…[16][17][18][19][20] Besides, DES, as a subclass of ionic liquids (ILs), is a green electrolyte for application in electroplating. [14][15][16][21][22][23] Reline, as one application of DES, is formed by choline chloride and urea at the ratio of 1:2. Harati et al fabricated successfully stoichiometric CIGS thin film by the one-pot electrodeposition in Reline as electrolyte.…”
mentioning
confidence: 99%
“…The HER interference can be overcome using non-aqueous electrolytes without complexing agents such as ionic liquids [71], ethylene glycol [72], and alcohol or alcohol/ionic liquid combinations [73]. Long et al reported electrodeposition of compact and quality CIGSe thin films at − 1.6 V/SCE using alcohol and LiCl electrolyte (pH 1.9-2.2) [74].…”
Section: Cise/cigse Electrodeposition In Non-aqueous Electrolytesmentioning
confidence: 99%
“…The increased supersaturated growth takes place over the same nucleation sites and hence results in the fine particles in porous/powdery deposits. Apart from DC depositions, there are other different plating techniques which includes pulse plating, pulse reverse plating and cyclic voltammetry techniques by which the secondary phase formation can be minimized [71,113,114]. Compared to conventional constant potential deposition techniques, electron charge transfer step is prevented in pulse plating as the deposition diffusion controlled process may lead thin films of large grain size morphology.…”
Section: Cigse Electrodeposition Schemes and Device Performancementioning
confidence: 99%
See 1 more Smart Citation